2021
DOI: 10.1590/1806-9649.2020v28e4769
|View full text |Cite
|
Sign up to set email alerts
|

Lean System: analysis of scientific literature and identification of barriers for implementation from a bibliometric study

Abstract: This article presents a bibliometric analysis on the Lean System over the period ranging from 2006 to 2017, showing the evolution of the publications over the years, the number of publications per country, the main journals, the most prolific authors, the most used keywords, and eventually barriers for the implementation of the Lean System. The greatest growth of publication rate occurred from 2014 to 2015. The countries with the most contribution have been the United Kingdom, the United States, and Sweden. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…coupling, coauthor were analyzed for keywords, for e.g., Zupic and Čater, 2015. The study relied on the citation indicator to find out the main keywords that studies focused on and prominent authors in Digital Finance and FinTech. To determine the network of research relationships between them, the practical stages of preparing the bibliometric study was carried out (study design, data collection, analysis, presentation, and guide); see Lobato et al (2021).…”
Section: Study Methods and Toolsmentioning
confidence: 99%
“…coupling, coauthor were analyzed for keywords, for e.g., Zupic and Čater, 2015. The study relied on the citation indicator to find out the main keywords that studies focused on and prominent authors in Digital Finance and FinTech. To determine the network of research relationships between them, the practical stages of preparing the bibliometric study was carried out (study design, data collection, analysis, presentation, and guide); see Lobato et al (2021).…”
Section: Study Methods and Toolsmentioning
confidence: 99%
“…One of the ways to identify similarities between multivariate observations is to apply clustering techniques [112,117]. Thus, the space of the columns in Table 6 was submitted to a hierarchical clustering algorithm, leading to the dendrogram presented in Figure 6.…”
Section: Stages Of the Evolution Of This Field Of Knowledgementioning
confidence: 99%
“…In order to overcome such obstacles, firstly, it is necessary to know them. Therefore, an enormous amount of research has been conducted around the world, to identify and classify such obstacles over the years [30][31][32][33][34][35][36][37][38][39][40][41]. The most recent systematic literature review, carried out over 450 articles [42], identified 27 barriers classified into six categories: financial/economic, market, cultural/social/behavioural, professional/technical, governmental, and technological.…”
Section: Introductionmentioning
confidence: 99%